The Developing Mathematics-Teaching Learning Devices Based on CORE to Increase Students' Ability to Communicate Mathematics - Winda Marhayani Wijaya, Putu; Wayan Puja Astawa, I; Gusti Putu Suharta, I (Journal of physics. Conference series, 2020)
This study was aimed to obtained mathematics-teaching learning devices (lesson plan, student's book, and teacher's guidance book) in focus on the subject of functions in X Grade that was made based on CORE. This study was a design research by Plomp (preliminary research, prototyping phase, and assessment phase). Data were collected by using validation sheets (validity assessment), learning process observation sheet, student's response questionnaire, teacher's response questionnaire (practicality assessment), and mathematical communication test (effectiveness assessment). The collected data were analyzed descriptively. The result of this research showed that developing mathematics-teaching learning devices are categorized: (1) valid, with average scores equal to 3.48; (2) practice, with average scores equal to 2.87, (3) effective, with average scores equal to 76.05. The student's book contained: (1) student's activity based on CORE; (2) real problem in daily life; (3) open ended questions and tasks to cultivate mathematical communication; (4) motivation text in every topic to support the students. The teacher's guidance book contained: (1) substance of lesson plan, student's book and its alternative solutions, (2) instruction in CORE learning. Based on these results, the developing mathematics-teaching learning devices is expected to increase students' ability to communicate mathematics